Penerapan Geostatistika Ordinary Kriging dalam Estimasi Harga Tanah (Studi Kasus: Kecamatan Samarinda Utara Kota Samarinda) - Mutiara Ayu Lestari; Piter Lepong; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Abstract Ordinary kriging geostatistical method is an interpolation method that used spatial data. This method generally used to estimate coal and mineral resources. However, over time this method is also used in estimating land prices. The purpose of this research is to determine the best model for land price estimation in North Samarinda District, especially in Sempaja Selatan Sub-District between spherical models, Exponential models and Gaussian models and to determine land price estimation using ordinary kriging geostatistical method based on the best semivariogram model displayed in the form of a contour map. The estimation process begins by create an experimental semivariogram and a structural analysis which is carried out to obtain sill, nugget and range. Then, interpolated using the three models to get the predicted value and calculated RMSE to determine the performance of the model, which the spherical model is the best model because it has the smallest RMSE value. From this method, a contour map of the estimation results of land prices in Sempaja Selatan Sub-District of North Samarinda District is obtained. The lowest land prices are found to be predominantly located in the northwest and north of Sempaja Selatan Sub-District. The lowest price of the land range from Rp. 279,000,- to Rp. 900,000,- per m2 and the highest price of land is predominantly located in the southern part of Sempaja Selatan Sub-District with prices ranging from Rp. 2,982,000, - to Rp. 4,981,000, - per m2. The variation in land prices in Sempaja Selatan Sub-District of North Samarinda District is influenced by physical factors, namely the elevation and slope of the slope. Low land prices tend to be in areas of high elevation and steep slopes, while high land prices are at low elevations and with a slope that is flat. So from this, it can be said that the land price is inversely proportional to the physical factor of the land.